A Review on Anticancer Heterocyclic Compounds Derivatives - Wassim Adam, Ruaa; Mohammed Sadiq, Hawraa; Lateef Razzaq, Zahraa; Neama Atiya, Rana; Abdul-Zahra, Alaa Jawad (Asian Pacific Journal of Cancer Biology, 2026)
Heterocyclic drugs are an important type of organic chemicals used in medicinal chemistry, particularly in anticancer drug discovery. Many newly authorized anticancer medicines have at least one heterocyclic core, demonstrating their structural variety and extraordinary capacity to interact with a wide range of biological targets. Furthermore, their presence in essential biomolecules such as DNA, RNA, vitamins, and alkaloids underscores their biological significance. This review points out current advances in the design, synthesis, and biological assessment of heterocyclic compounds with anticancer properties. Nitrogen-, oxygen-, and sulfur-containing heterocycles are studied in broad terms, such as benzimidazoles, pyrazoles, triazoles, quinoxalines, coumarins, oxadiazoles, and metal-heterocycle complexes. The topic includes their methods of action, structure-activity relationship (SAR) insights, cytotoxic assessment findings, and selectivity patterns. Overall, the findings highlight the vital significance of heterocyclic structures as platforms for generating safer and more effective anticancer drugs.